Incidence of Daytime Sleepiness and Associated Factors in Two First Nations Communities in Saskatchewan, Canada - Chandima Karunanayake; James Dosman; Donna Rennie; Joshua Lawson; Shelley Kirychuk; Mark Fenton; Vivian Ramsden; Jeremy Seeseequasis; Sylvia Abonyi; Punam Pahwa; The First Nations Lung Health Project Research Team (Clocks & Sleep, 2018)
Excessive daytime sleepiness (EDS) is the tendency to sleep at inappropriate times during the day. It can interfere with day-to-day activities and lead to several health issues. The objective of this study was to investigate the association between income, housing conditions, and incidence of EDS in adults living in two Cree First Nations communities. The data for this study involved 317 individuals aged 18 years and older who participated in baseline and follow-up evaluations (after four years) of the First Nations Lung Health Project, which was conducted in Saskatchewan in 2012–2013 and 2016. Both at baseline and follow-up survey after four years, an Epworth Sleepiness Scale (ESS) score >10 was considered to be abnormal. Logistic regression models were used to assess relationships between abnormal ESS and covariates at baseline. In 2016, 7.6% (24/317) of the participants reported an ESS >10 with the mean being 12.8 ± 2.0. For the same group, the mean ESS at baseline was 6.9 ± 2.2. The incidence of subjective EDS based on the ESS >10 was estimated at 7.6% over four years. This study showed an association between incidence of subjective EDS and less money left over at end of the month, having a house in need of repairs, having water or dampness in the past 12 months, and damage caused by dampness.